Pituitary Adenoma with Apoplexy with Arteriovenous Malformation - Bansal, Rajeev; Shekhawat, Jitendra; Purohit, Devendra (Indian Journal of Neurosurgery, 2017)
Background This is a rare association of pituitary adenoma with apoplexy with arteriovenous malformation as only single case was reported prior to this case as per our knowledge.Case Description A 25-year-old man presented with chief complaints of headache of sudden onset, severe in intensity with sudden loss of vision. Imaging shows pituitary adenoma with apoplexy with right parietal arteriovenous malformation. The patient was managed with embolization for parietal arteriovenous malformation and medically for pituitary adenoma with apoplexy.Conclusion Pituitary apoplexy can be treated conservatively if no features of mass effect present. Follow-up of the patient must be done regularly to look for the size of pituitary adenoma and recurrence of arteriovenous malformation.
Keywords: arteriovenous malformation; pituitary adenoma; primary brain tumor